Insulin-like growth factor II mRNA-binding protein 3 (IMP3) expression in hepatocellular carcinoma: a clinicopathological analysis with emphasis on diagnostic value - Wachter, David Lukas; Breuhahn, Kai (Histopathology, 2012)
Wachter D L, Kristiansen G, Soll C, Hellerbrand C, Breuhahn K, Fritzsche F, Agaimy A, Hartmann A & Riener M-O (2012) Histopathology 60, 278-286 Insulin-like growth factor II mRNA-binding protein 3 (IMP3) expression in hepatocellular carcinoma. A clinicopathological analysis with emphasis on diagnostic value Aims: Patients with hepatocellular carcinoma (HCC) usually present with advanced disease and rarely qualify for curative therapy. Immunohistochemical markers that help to discriminate benign from malignant processes early, and that have prognostic significance, would be useful. Expression of the oncofetal protein insulin-like growth factor II mRNA-binding protein 3 (IMP3) in malignant cells of different tumour types correlates with reduced overall survival. Methods and results: Tissue microarrays (TMAs) containing 55 normal liver samples, 365 HCCs (122 with corresponding non-tumorous liver), 10 hepatocellular adenomas, 13 focal nodular hyperplasias and nine dysplastic nodules from western European patients were stained for IMP3. IMP3 was analysed in 61 core needle biopsies and findings were compared to glypican-3 and CD34. HCCs in TMAs were strongly positive for IMP3 in 18.4% of cases compared to absent expression in normal and non-tumorous liver tissue and benign liver tumours. Patients with IMP3 expression in HCCs showed significantly poorer overall survival in multivariate analysis (P = 0.044). Of the 61 core needle biopsies analysed, 32 (52.5%) of the HCCs were IMP3-positive. Conclusions: In core needle biopsies, IMP3 expression seems to be of limited use as a single marker for the diagnosis of HCC, given a sensitivity of 52%, but it may be helpful in combination with other markers.